Opportunities and Challenges in Implementing Halal Tourism Destinations in the Lake Toba Parapat Area, Simalungun Regency - Sonya Melinda Nasution; Fauzi Arif Lubis; Chuzaimah Batubara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This research attempts to analyze problems, and solutions by looking at opportunities and challenges in implementing halal tourism destinations in the Parapat area of Lake Toba. This is in order to increase tourist visits to increase local revenue, because the large potential for halal tourism has an impact on the regional economy, especially for the Simalungun district government. The qualitative approach through the research method used is the QSPM (Quantitative Strategic Planning Matrix) method. The results of this study conclude that the most influential opportunities for the advancement of tourist destinations in the Parapat Lake Toba area are implementing cashless payments so that they are practical and efficient. Seeing the progress of fintech, such as digital wallets, makes non-cash payments even more advanced. And several opportunities can be utilized for progress in halal tourism destination businesses in the Parapat Lake Toba area, Simalungun Regency, namely the growth of the tourism industry in the Parapat Lake Toba area, Simalungun Regency, is very high, the Parapat Lake Toba tourism destination has great potential for regional economic development, Cooperation between tickets tour with lodging around the Parapat Lake Toba destination, Simalungun Regency, integration with a digital transaction storage system to increase tourist visits and the government strongly supports halal-based businesses in the Parapat Lake Toba area, Simalungun. The challenge faced in implementing this halal tourism destination is that there is an understanding that halal tourism is not a large market share so that its application is less than optimal. Furthermore, the challenges faced in implementing halal tourism which are referred to in the results of the SWOT analysis are the lack of public or visitor awareness of the importance of preserving culture, art, and history.